Environmental conditions impacting juvenile Chinook salmon growth off central California: An ecosystem model analysis. Issue 8 (23rd April 2015) - Fiechter, J.; Huff, D. D.; Martin, B. T.; Jackson, D. W.; Edwards, C. A.; Rose, K. A.; Curchitser, E. N.; Hedstrom, K. S.; Lindley, S. T.; Wells, B. K.
Abstract A fully coupled ecosystem model is used to identify the effects of environmental conditions and upwelling variability on growth of juvenile Chinook salmon in central California coastal waters. The ecosystem model framework consists of an ocean circulation submodel, a biogeochemical submodel, and an individual‐based submodel for salmon. Simulation results indicate that years favorable for juvenile salmon growth off central California are characterized by particularly intense early season upwelling (i.e., March through May), leading to enhanced krill concentrations during summer near the location of ocean entry (i.e., Gulf of the Farallones). Seasonally averaged growth rates in the model are generally consistent with observed values and suggest that juvenile salmon emigrating later in the season (i.e., late May and June) achieve higher weight gains during their first 90 days of ocean residency.